Comparative Analysis of Gut Microbiota in Captive and Wild Oriental White Storks: Implications for Conservation Biology - Wu, Hong; Wu, Fang-Ting; Zhou, Qi-Hai; Zhao, Da-Peng (Frontiers in Microbiology, 2021)
The oriental white stork (Ciconia boyciana) is considered an endangered species based on the International Union for Conservation of Nature (IUCN) Red List. This study presents the first evidence on comparative analysis of gut microbial diversity of C. boyciana from various breeding conditions. To determine the species composition and community structure of the gut microbiota, 24 fecal samples from Tianjin Zoo and Tianjin Qilihai Wetland were characterized by sequencing 16S rRNA gene amplicons using the Illumina MiSeq platform. Firmicutes was found to be the predominant phylum. Analysis of community structure revealed significant differences in the species diversity and richness between the populations of the two breeding conditions. The greatest α-diversity was found in wild C. boyciana, while artificial breeding storks from Tianjin Zoo had the least α-diversity. Principal coordinates analysis showed that the microbial communities were different between the two studied groups. In conclusion, this study reveals the species composition and structure of the gut microbiota of oriental white storks under two breeding conditions, and our findings could contribute to the integrative conservation of this endangered bird.